Release of Ammonium-N (NH4+) and Nitrate-N (NO3-) by different Leguminous Cover Crops (LCC) planted in peat soils / Muhammad Rahmat Abdul Rahman - Abdul Rahman, Muhammad Rahmat (Faculty of Plantation and Agrotechnology, 2019)
Peat soils is renowned for the low mineral-N concentration which is crucial for crop’s growth. One of the most effective and conserving method to improve the soil mineral-N concentration is by planting leguminous cover crops (LCCs) which is common in oil palm plantation area. However, different LCCs were found to release different concentration of mineral-N into the soils. Hence, this study aims to determine the concentration of mineral-N in form of ammonium-N (NH4+) and nitrate-N (NO3-) released by different types of LCCs namely Mucuna bracteata, Calopogonium mucunoides, Pueraria javanica and Centrosema pubescens as well as to evaluate the effects on physico-chemical properties of peat soils. Results showed that Mucuna bracteata released a significant amount of ammonium-N (NH4+) into the soils and shows a vigorous growth compared to other LCCs. It is suggested that most of the LCCs can survive in acidic peat condition whilst improving the concentration of ammonium-N (NH4+) and nitrate-N (NO3-).